2007
DOI: 10.1177/1545968306292608
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Motor Imagery and Physical Practice in Group Treatment Applied to Subjects With Parkinson’s Disease

Abstract: The combination of motor imagery and real practice may be effective in the treatment of PD, especially for reducing bradykinesia. The implementation of this treatment regimen allows for the extension of practice time with negligible risk and low cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
1
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(217 citation statements)
references
References 36 publications
2
205
1
9
Order By: Relevance
“…Moreover, most of the PD patients in the initial stages preserve the vivacity and the precision of the motor image. 1,10,11 The result of the researches with MP are still controversial, due to many reasons, like small sample sizes, sample heterogeneity, and mainly the diversity of study protocols. The MP interventional protocols are cognitively complex and challenging, proposing variations in their application concerning the MP type, tasks/movements to be imagined, and instruction type.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of the PD patients in the initial stages preserve the vivacity and the precision of the motor image. 1,10,11 The result of the researches with MP are still controversial, due to many reasons, like small sample sizes, sample heterogeneity, and mainly the diversity of study protocols. The MP interventional protocols are cognitively complex and challenging, proposing variations in their application concerning the MP type, tasks/movements to be imagined, and instruction type.…”
Section: 8mentioning
confidence: 99%
“…In three studies, 10,12,13 patients of both sex, with idiopathic PD at light to moderate degree of the disease, and balanced ages once allocated in Control Group (CG) and Experimental Group (EG) composed the sample. Another study 2 that assessed a sample of patients with degree varying from light to severe, performed intention-to-treat analysis reporting the initial mean age, but failed to inform the mean age per sex group of the patients who completed all the steps of the study.…”
mentioning
confidence: 99%
“…Gli studi riportano prove dell'efficacia della riabilitazione basata sulle immagini motorie in casi di malattia di Parkinson, dolore cronico, dolore connesso all'arto fantasma, ictus (Birbaumer et al, 1997;Chan et al, 2007;Tamir et al, 2007;Malouin et al, 2012). Come accennato in precedenza, un fattore determinante per la riuscita del training basato sulle immagini motorie è l'integrità dei processi di base dell'imagery nei pazienti.…”
Section: Applicazioni Delle Immagini Mentali In Riabilitazioneunclassified
“…As such, it is not unlikely that the nigrostriatal dopaminergic deficiency of PD may affect imagery performance. Up to now, however, studies on this topic are scarce and have reported largely inconsistent results (Heremans, et al, 2011;Tamir, et al, 2007;Yagüez, Canavan, Lange, & Hömberg, 1999).…”
Section: Motor Imagery As a New Therapy Tool Within Neurological Rehamentioning
confidence: 99%
“…In the past, most studies did not evaluate MI ability at all (e.g., Liu, et al, 2004;Tamir, et al, 2007), or evaluated it by means of subjective methods such as questionnaires and interviews (e.g., Page, Levine, Sisto, & Johnston, 2001). An exception to this are studies that used the recording of autonomic responses to evaluate MI (see Collet, et al, 2011 andCollet, 2005a for reviews).…”
Section: Evaluation Of Motor Imagery Abilitymentioning
confidence: 99%